Review of Factors Influencing the Impact of Access to Sanitation Facilities on Stunting - Alfan Ridha; Muhammad Zainul Maarif; Titik Dwi Noviati; Yuniars Renowening; Himmatunisa Mahmudah; Rosmauli Jerimia Fitriani (Sean Institute, 2023)
Stunting is a condition where a child's height is not appropriate for their age. In 2022, an estimated 21.6% of children under the age of 5 in Indonesia were affected by stunting. Stunting is a complex nutritional problem influenced by various factors, including the environment. Several studies have examined the relationship between household hygiene and sanitation factors and growth retardation in young children. The aim of this research is to analyze the risk factors associated with personal hygiene and sanitation practices of parents or guardians within households in Indonesia. The research methodology employed in this study is a literature review. A total of 20 selected articles from the Garuda Jurnal and Sinta databases between 2019 and 2022 were evaluated based on publication criteria, namely freely available original research articles where at least one variable analyzed hygiene and sanitation in relation to child growth. The findings of this research were synthesized using the PRISMA method. The articles were grouped based on similar findings to address the research question. This study found that handwashing, access to clean water, toilet sanitation, and the occurrence of diarrhea were associated with the risk of stunting. The conclusion drawn from this research is that most studies indicate a relationship between personal hygiene and sanitation facilities and the occurrence of stunting. For future research, the use of systematic reviews and meta-analyses is recommended.